PANDANGAN KONTROVERSIAL IBN HAZM DALAM BIDANG FIQIH - Subhan M.A Rachman (State Islamic University North Sumatra, 2009)
Abstract: Ibn Hazm’s Controvertial Views on Islamic. Ibn Hazm was one of the reknown scholars of Islamic Spain whose major contribution as an intellectual was in the field of law. He became very popular and influential for maintaining many legal opinions different from those of others. As such he became a controversial figure in the field whose opinions are still subject of heated debates up to the present. This article revisits some of Ibn Hazm’s opinion on a number of legal issues.Kata Kunci: Ibn Hazm , fiqih, kontroversi